Using Thermogravimetry as a Simple Tool for Nutrient Assessment in Fire Affected Soils. (12th May 2017) - Neris, Jonay; Doerr, Stefan H.; Tejedor, Marisa; Jiménez, Concepción; Hernández‐Moreno, José M.
Abstract: Nutrient availability can be a limiting factor in the recovery of ecosystems after wildfire. Its evaluation is therefore critical for selecting appropriate restoration strategies in the post‐fire period. This study explores, for the first time, the use of thermogravimetry (TG) as a rapid proxy for nutrient availability and soil recovery. Soil samples from five burned and unburned sites in Andisols of Tenerife (Spain) were selected to examine the medium‐term impact of fire. Key soil chemical parameters [pH, electric conductivity, cation exchange capacity (CEC), main cation and anions in the soil solution, total organic carbon (TOC), total nitrogen (TN) and available phosphorus] were determined and thermogravimetry performed. Burned soils showed significantly higher pH, Ca 2+ and Mg 2+ and a lower CEC, TOC and TN than the unburned counterparts, and a site‐dependent response for soluble SO4 2− and available phosphorus was observed in the medium term. Time elapsed since fire could have masked additional fire impacts. Thermogravimetry data allowed reasonable prediction of most soil properties and parameters, with r 2 ranging from 0·4 to 0·9. The results demonstrate that soluble nutrient content is directly related to the amount of ash in the soil. The decrease of labile carboxyl‐C was associated with an increase of pH and decrease of CEC, whereas the increase of recalcitrant and refractory pools was associated with the amount of TOC and TN. The results suggest that this novel application of an established method can provide, following an initial calibration step, rapid and inexpensive proxies for key parameters necessary for assessing fire‐induced ecosystem degradation and designing suitable restoration strategies in the post‐fire period. Copyright © 2017 John Wiley & Sons, Ltd.